2006
DOI: 10.1037/1040-3590.18.4.402
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of alcohol-related consequences among high school and college students: Application of item response models to the Rutgers Alcohol Problem Index.

Abstract: The Rutgers Alcohol Problem Index (RAPI; H. R. White & E. W. Labouvie, 1989) is a frequently used measure of alcohol-related consequences in adolescents and college students, but psychometric evaluations of the RAPI are limited and it has not been validated with college students. This study used item response theory (IRT) to examine the RAPI on students (N = 895; 65% female, 35% male) assessed in both high school and college. A series of 2-parameter IRT models were computed, examining differential item functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
139
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(152 citation statements)
references
References 36 publications
8
139
5
Order By: Relevance
“…Students were asked to report the frequency of various problems with drinking in the past 12 months (e.g., "caused shame or embarrassment to someone," "kept drinking when you promised yourself not to"). Each of the 18 items was dichotomized into never (score of 0) versus one or more times (score of 1) and these scores were summed, similar to summing in other studies demonstrating good construct validity (Cohn et al, 2011;Neal et al, 2006). Those who did not report consuming any alcohol in the past 12 months were coded as having 0 alcohol consequences.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Students were asked to report the frequency of various problems with drinking in the past 12 months (e.g., "caused shame or embarrassment to someone," "kept drinking when you promised yourself not to"). Each of the 18 items was dichotomized into never (score of 0) versus one or more times (score of 1) and these scores were summed, similar to summing in other studies demonstrating good construct validity (Cohn et al, 2011;Neal et al, 2006). Those who did not report consuming any alcohol in the past 12 months were coded as having 0 alcohol consequences.…”
Section: Methodsmentioning
confidence: 99%
“…Internal consistency was strong ( = .90). A cutoff score of 8 distinguished those with problematic alcohol use (Neal et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…A primary advantage of IRT is the ability to statistically model observable manifestations of a hypothesized underlying trait; in this case, alcohol problem severity (Embretson and Reise, 2000). Further, IRT can provide information about how well an item places an individual on a specifi c point along the alcohol problem severity continuum (Embretson and Reise, 2000;Neal et al, 2006), and because it is not sample dependent, IRT assumptions maintain that replication of fi ndings will be consistent across similar samples (Embretson and Reise, 2000). IRT methods can also tell us which consequences reliably assess the range and severity of problems experienced by fi rst-year college women and can assist in ascertaining which consequences may be "biased," in the sense of accurately discriminating among individuals with higher and lower levels of problem severity.…”
Section: H Eavy Episodic Drinking Among Collegementioning
confidence: 99%
“…[49][50][51] Responses were scored dichotomously and summed (range: 0-18) 51 ; previous research found that scores $8 indicate an alcohol use disorder. 51 …”
mentioning
confidence: 99%